2013
DOI: 10.1073/pnas.1311325110
|View full text |Cite
|
Sign up to set email alerts
|

Extrahelical (CAG)/(CTG) triplet repeat elements support proliferating cell nuclear antigen loading and MutLα endonuclease activation

Abstract: MutLα endonuclease can be activated on covalently continuous DNA that contains a MutSα- or MutSβ-recognizable lesion and a helix perturbation that supports proliferating cell nuclear antigen (PCNA) loading by replication factor C, providing a potential mechanism for triggering mismatch repair on nonreplicating DNA. Because mouse models for somatic expansion of disease-associated (CAG) n /(CTG) n triplet repeat sequences have implicated both MutSβ and MutLα and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
114
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(121 citation statements)
references
References 44 publications
(67 reference statements)
7
114
0
Order By: Relevance
“…Intriguingly, Rogacheva et al (2014) demonstrated that yeast Mlh1-Mlh3 enhances Msh2-Msh3 DNA-binding activity, while Msh2-Msh3 stimulates Mlh1-Mlh3 endonuclease activity. Therefore, enhanced Msh2-Msh3 binding to TNR structures could inappropriately recruit Mlh1-Mlh3 during replication or outside of S phase and stimulate its endonuclease activity, leading to gap formation and DNA repair synthesis that incorporates incremental expansions (Gomes-Pereira et al 2004;Pluciennik et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, Rogacheva et al (2014) demonstrated that yeast Mlh1-Mlh3 enhances Msh2-Msh3 DNA-binding activity, while Msh2-Msh3 stimulates Mlh1-Mlh3 endonuclease activity. Therefore, enhanced Msh2-Msh3 binding to TNR structures could inappropriately recruit Mlh1-Mlh3 during replication or outside of S phase and stimulate its endonuclease activity, leading to gap formation and DNA repair synthesis that incorporates incremental expansions (Gomes-Pereira et al 2004;Pluciennik et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, the Msh2 ATPase domain (abolishing ATPase activity but not DNA-binding ability) was shown to be directly involved in trinucleotide repeat expansions, strongly suggesting that a functional MutS complex was indeed required for such expansions [35]. Finally, it was recently demonstrated that two or three extrahelical CAG or CTG triplets were sufficient to trigger MutL activation, and depended on MutS function [39]. All these data point to a model in which MMR complexes recognize and bind secondary structures associated to CAG/CTG repeats, maybe stabilizing these structures, and that such binding leads to expansions, by a process requiring a functional MMR activity.…”
Section: Introductionmentioning
confidence: 99%
“…Recent in vitro studies of eukaryotic MMR indicate that in these MutH-free organisms, detection of a mismatch by MutS or MutSα [MutS(α)] licenses MutL(α) to interact with the processivity factor (β-clamp/PCNA), which in turn activates the latent endonuclease activity of MutL(α) to incise the daughter DNA strand on both the 3′ and 5′ sides of the error (8)(9)(10)(11). The interaction between MutL and the β-clamp (or between MutLα and PCNA) provides the strand discrimination signal because the β-clamp (or PCNA) is loaded asymmetrically at the replication fork or at a nick in DNA (10,12).…”
mentioning
confidence: 99%
“…Other models include trapping of MutS(α) clamps near the mismatch by MutL(α) followed by DNA looping or, alternately, MutS(α)-induced polymerization of MutL(α) along the DNA to reach the strand-discrimination signal (6,7,15,18,22). Some degree of localization to the mismatch is suggested by in vitro studies of eukaryotic MMR proteins, indicating that although MutLα can introduce nicks across long stretches of DNA, they occur preferentially in the vicinity of the mismatch (9,11,12).…”
mentioning
confidence: 99%